Comics using problem-based learning in science subject: a systematic literature review - Shaafi, Nur Farha; Sharif, Sabariah; Mohd Yusof, Mohammad Mubarrak; Jumi, Mohd Jusmaime (Universiti Teknologi MARA, Kedah, 2025)
In the 21st century, comic-based learning has emerged as a promising method to enhance engagement in science education. However, research on its effectiveness remains lacking, with very few studies offering a comprehensive synthesis. This systematic review addresses that gap by evaluating how comics are used to support teaching and learning in science. In this review, we assessed its utility and effectiveness, focusing on its impact on students and teachers. To write this review, we followed four systematic steps: planning research questions, conducting a literature search via Scopus, Web of Science (WOS), ProQuest, ERIC, and Google Scholar, evaluating and selecting published studies, and synthesizing findings. The literature search was limited to publications from 2015 to 2024, and focused on themes of learning, comics, and science. Our findings indicate that comic-based learning is applied across all educational levels, i.e., primary, secondary, and higher education and yielded positive outcomes, such as improved conceptual understanding, student motivation, classroom engagement, and critical thinking. Overall, comics serve as an interactive, visually engaging tool for problem-based learning, aiding both students and educators. This review contributes valuable insights to the